Journalism and public opinion according to a number of studies and the theory of reliance on the media - Alshamsi, Huda (Journal of Humanities & Social Sciences, 2021)
This research aimed at reveal the role that the press plays in shaping the knowledge and attitudes of individuals in any issue, and to explain this in light of the theory of dependence on media that are concerned with the motives and causes of the public’s dependence on the media and the effects that this dependence has on Knowledge, opinions, trends and behavior, as I collected 19 scientific studies on the same topic through which we emphasize the role of the media in drawing public opinion, which is determined based on the articles that are published and they represent the facts that the reader gets, and the countries on which the studies were taken varied. According to different topics.